The semantics of homoeopathy - Guajardo, Germán; Searcy, Roberto; Reyes, Oscar (British Homeopathic Journal, 1994)
Homoeopathy is often referred to as a form of ‘alternative’ or ‘complementary’ medicine. This results in the marginalization of homoeopathy and tends to equate allopathy with medicine. In fact homoeopathy is a medical speciality and our semantics should reflect this: There is a need to improve our courses and incoporate interdisciplinary topics. The use of the terms dilution and potency is also discussed.
Keywords: Semantics; Alternative; Complementary; Allopathy; Speciality; Medical science